Stability and flow of hot asphalt mixes incorporating steel slags - Calva Herrera, Leyner Oswaldo (2022)
The present investigation was based on the innovation and elaboration of a hot asphalt mix (HMA) due to the premature deterioration of flexible pavements, and low capacity to fulfill its useful life. Then, it is recognized the need to ensure a good quality of materials for the asphalt mix and a search for a new material that can give greater durability and avoiding premature deterioration of the pavement. Thus, the incorporation of steel slag for the HMA design was evaluated with the objective to determine the stability and flow of the hot asphalt mixture incorporating steel slags. To achieve this, the Marshall methodology was developed with a percentage of steel slag with respect to the coarse aggregate in 0% - 15% - 25% - 50% - 75%. The results obtained, in terms of quality of the aggregates, complied with the standards of quality. It was concluded that the modified asphalt mixture with 15% steel slag is the best combination, in the same way this percentage complies for light-medium traffic, the remaining combinations (25% - 50% - 75%) only comply for light traffic. It was possible to increase the stability and flow of the incorporated asphalt mixture up to a maximum of 25% for a HMA with respect to the control mixture.